The role of sustainable entrepreneurship in sustainability transitions: A conceptual synthesis against the background of the multi-level perspective - Jacob Hörisch (Administrative Sciences, 2015)
This paper conceptually synthesizes prior studies on sustainable entrepreneurship against the background of the multi-level perspective. It thereby relates separate streams of literature on sustainable entrepreneurship, sustainability transformations and ecopreneurship, which have previously not been systematically connected and synthesized, to the multi-level perspective. The paper furthermore provides suggestions on how the multi-level perspective can be advanced based on the inspirations of these previously only sparsely-connected streams of literature. Finally, implications for entrepreneurs, academia and politics are presented: means to increase the contribution of sustainable entrepreneurship to sustainability transitions are suggested, and the importance of growth and degrowth is discussed in the context of sustainable entrepreneurship.
Keywords: 350; sustainable entrepreneurship; multi-level perspective; sustainability transitions; ecopreneurship; sustainable development; degrowth; transformation